The Effect of Spiritual Emotional Freedom Technique on Anxiety Levels of Non-Hemorrhagic Stroke Patients: A Study at RSD Gunung Jati Cirebon - Rahmadhani, Andra; Syaripudin, Ahmad; Romadhon, Lily Wahyuni (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Non-hemorrhagic stroke can cause both physical and mental problems, one of which is anxiety. Unresolved anxiety can hinder patient recovery. A holistic nursing approach is needed, one of which is the Spiritual Emotional Freedom Technique (SEFT). This study aims to implement SEFT therapy to reduce anxiety in non-hemorrhagic stroke patients in the Stroke Unit Room at RSD Gunung Jati Cirebon. Method: A descriptive method with a case study approach involved one respondent diagnosed with non-hemorrhagic stroke. Data were collected using observation sheets and questionnaires. Result: A three-day case study showed a decrease in anxiety score from 27 (moderate anxiety) to 8 (no anxiety). Conclusion: SEFT therapy has the potential as an effective non-pharmacological approach to reduce anxiety in non-hemorrhagic stroke patients and can be implemented in nursing care by actively involving patients and their families.